A study on the wear behavior of tin-based journal bearing under different working conditions. Issue 3 (1st October 2019) - Li, Hulin; Yin, Zhongwei; Wang, Yanzhen
Abstract : Purpose: The purpose of this paper is to study the friction and wear properties of journal bearings under different working conditions. Design/methodology/approach: Friction coefficient and wear losses of journal bearing under different working conditions have been determined by a bearing test rig. The worn surfaces of bearing were examined by scanning electron microscopy and laser three-dimensional micro-imaging profile measurements, and the tribological behavior and wear mechanisms were investigated. Findings: The wear loss and friction coefficient of bearing under starting-stopping working condition is far greater than that of steady-state working conditions. In addition, the maximum wear loss under start-up and stop conditions is about 120 times of that under stable operating conditions. Under stable working conditions, the main wear forms of bearings are abrasive wear, under starting-stopping working conditions the main wear mechanisms of bearings are adhesion wear, abrasive wear and fatigue wear. Originality/value: These research results have certain practical value for understanding the tribology behavior of journal bearings under different working conditions.